Biossorção de metais tóxicos por Saccharomyces cerevisiae - Rossi, Andreia de (2015)
Contamination by toxic metals has become one of the most serious environmental problems of today. The biosorption with biomaterials is a low-cost technology, effective and easy to apply. Saccharomyces cerevisiae is a promising biosorbent due to its chemical nature and being produced in large scale by the microorganism to be responsible for the alcoholic fermentation process used in industries for drinks and fermented and distilled alcoleira industry, waste or by-product being such industry. Although many papers have reported the use of biomass for biosorption of toxic metals, few have studied the encapsulation processes of biomass or the use of biosurfactants as supporting the biosorption. Thus, the aim was to use the yeast S. cerevisiae as biosorbent of toxic metals. First were built isotherms for chromium (VI) biosorption using commercial yeast, which is submitted or not to thermal or chemical treatments with alkalis. After the biosorption the tests with biosorbent obtained from beer industry encapsulated sodium alginate were performed. The biosorbent characterization before and after the immobilization process by chemical composition was performed, determining the point of zero charge, and chemical and morphological characterization. End the influence of the addition of biosurfactants in biosorption. Subsequently, the pH study for the adsorption of cadmium, lead and chromium (VI) ions to construct the adsorption isotherms was carried out. For the conditions that showed the best results for the adsorption of chromium (VI) was carried out to characterize the adsorbents before and after the process using SEM, FTIR and EDX. In a last step, it was used the best conditions determined in previous tests for the biosorption of chromium (VI) using real effluent. In the initial study of commercial yeast under different treatments for biosorption of chromium (VI), it was observed that the untreated yeast showed the highest adsorption capacity, 8.05 mg g-1 compared to 7 mg g-1 and 5 mg g-1 in the yeast treated with the chemical and thermal treatments, respectively. The biosorbent showed adsorption capacity of 7.9 mg g-1, compared with 14.9 mg g-1, where the addition of biosurfactant obtained from commercial biomass S. cerevisiae was performed, which is an increase of 60 % in biosorption capacity in 24 h. At pH study to biosorption process with alginate encapsulated yeast in the presence of biosurfactant, the best pHs were 5.0 to cadmium and lead and 2.0 to chromium (VI). The adsorption capacities of ions were 178 mg g-1 lead, represented by Langmuir isotherm model; 38 mg g-1 to cadmium, represented by BET isotherm model. In studies carried out with chromium (VI) the maximum capacity reached was 72 mg g-1 at 25 °C. In real effluent, the maximum capacity of chromium biosorption (VI) was 34.76 mg g-1, where in the equilibrium data were represented by BET isotherm model. In the morphological analysis and chemical composition performed confirmed the presence of chromium on the surface and inside of the biosorbent. The metallic ions biosorption by-product of beer industry after encapsulation in sodium alginate and using biosurfactant obtained from the same organism as an adjuvant is efficient and can be used in wastewater treatment